2005
DOI: 10.1182/blood-2004-07-2807
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hemochromatosis is reflected in the iron isotope composition of blood

Abstract: It has recently been shown that the iron isotopic composition of blood differs between individuals and sexes, which is supposed to reflect individual differences in iron metabolism. We hypothesized that patients suffering from hereditary hemochromatosis would demonstrate alterations in the iron isotopic composition of blood due to persistent up-regulation of intestinal iron absorption. Blood from 30 patients with homozygous C282Y hemochromatosis was analyzed for iron isotopic composition by a newly developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 28 publications
2
67
2
Order By: Relevance
“…Of 86 hemochromatosis patients included in the study, 73 presented with clinical manifestations and 13 were identified by family screening. Some of the hemochromatosis patients were previously included in a study investigating the iron isotope composition of blood (47 ).…”
Section: Study Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 86 hemochromatosis patients included in the study, 73 presented with clinical manifestations and 13 were identified by family screening. Some of the hemochromatosis patients were previously included in a study investigating the iron isotope composition of blood (47 ).…”
Section: Study Patientsmentioning
confidence: 99%
“…We used atomic-absorption photometry to measure iron concentration in dry liver tissue from 30 patients and assessed hepatic iron index as iron concentration of dry liver tissue (mol/g) divided by the age of the patient (years). A total of 73 patients had completed iron depletion therapy at least 2 years before the study, and their need for iron removal to prevent reaccumulation was assessed from mean amounts of blood removed by phlebotomy per year during maintenance therapy (47 ).…”
Section: Assessment Of Variables Reflecting Iron Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[14]. Natural iron isotope variations in the blood may serve to identify differences in intestinal iron absorption between individuals and genotypes [15]. Moreover, 57 Fe and 58 Fe have already been used as tracers in nutritional studies on humans due to their low natural abundance [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…244 Also for Zn, slight differences in the isotopic composition were demonstrated using MC-ICP-SFMS measurements between different body compartments. View Online owing to the fact that the production of 206 Pb, 207 Pb and 208 Pb as a result of the decay of 238 U, 235 U and 232 Th, respectively, has been going on for a much longer time in the crust.…”
Section: Biological Samplesmentioning
confidence: 99%